Axonal damage in spinal cord is associated with gray matter atrophy in sensorimotor cortex in experimental autoimmune encephalomyelitis. (March 2020) - Meyer, Cassandra E; Gao, Josephine L; Cheng, James Ying-Jie; Oberoi, Mandavi R; Johnsonbaugh, Hadley; Lepore, Stefano; Kurth, Florian; Thurston, Mackenzie J; Itoh, Noriko; Patel, Kevin R; Voskuhl, Rhonda R; MacKenzie-Graham, Allan
Background: Gray matter (GM) atrophy in brain is one of the best predictors of long-term disability in multiple sclerosis (MS), and recent findings have revealed that localized GM atrophy is associated with clinical disabilities. GM atrophy associated with each disability mapped to a distinct brain region, revealing a disability-specific atlas (DSA) of GM loss. Objective: To uncover the mechanisms underlying the development of localized GM atrophy. Methods: We used voxel-based morphometry (VBM) to evaluate localized GM atrophy and Clear Lipid-exchanged Acrylamide-hybridized Rigid Imaging-compatible Tissue-hYdrogel (CLARITY) to evaluate specific pathologies in mice with experimental autoimmune encephalomyelitis (EAE). Results: We observed extensive GM atrophy throughout the cerebral cortex, with additional foci in the thalamus and caudoputamen, in mice with EAE compared to normal controls. Next, we generated pathology-specific atlases (PSAs), voxelwise mappings of the correlation between specific pathologies and localized GM atrophy. Interestingly, axonal damage (end-bulbs and ovoids) in the spinal cord strongly correlated with GM atrophy in the sensorimotor cortex of the brain. Conclusion: The combination of VBM with CLARITY in EAE can localize GM atrophy in brain that is associated with a specific pathology in spinal cord, revealing a PSA of GM loss.